النقل البحري وأهميته بالنسبة للاقتصاد السوري (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يوضح هذه الدراسة أهمية النقل البحري بالنسبة للاقتصاد السوري، والموقع الهام الذي تحتله التجارة الخارجية بالنسبة للبلدان النامية بشكل عام و في سورية بشكل خاص، وتظهر تأثير النقل البحري في  التجارة الخارجية بالنسبة لهذه البلدان،كما تعرض هذه الدراسة للآثار المتحصلة من إنشاء أسطول تجاري بحري أو التوسع في عدد الوحدات البحرية التجارية. كما تبين الدور الذي يقوم به النقل البحري في سوريا بالنسبة للتجارة الخارجية من خلال التعرض لحجم الصادرات و الواردات السورية عبر الموانئ خلال الفترة مابين عامي 2000-2006. وتحلل طبيعة هذه الصادرات و الواردات وبيان نسبة كل منها إلى الآخر لتظهر طبيعة الاقتصاد السوري الذي يعتمد في صادراته على المواد الأولية وفي وارداته على السلع الرأسمالية بشكل رئيسي. ثم في النهاية يتم التطرق لمجموعة من النتائج والتوصيات التيتم استخلاصها من هذا البحث.   transportation importance for Syrian economics, and it can appear the important position of the out siding trading for growing countries at all and specially for Syria, in addition to the marine transportation effects on the out siding trading of those countries, and this study explain the effects of building a trading marine fleet or increase trading ships count. It can appear the situation of the Syrian marine transportation for the out siding trading through sliding the count of Syrian imports and exports at Syrian ports during the time from (2000-2006). The study analyses imports and exports nature and their percent to each other to appear the Syrian economic nature that depends on its exports on elemental subjects and depends on its imports on capitalist goods mainly. Finally we have a group of results and suggestions that extraction from this research.